Students' Perceptions, Creative Thinking Skills, and Practicum Results in Online and Offline Models - Wahyu Prihanta; Elly Purwanti (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This study aims to describe perceptions, practicum results, and students' creative thinking skills in online and offline practicums. This research is ex post facto. The subjects of this study were 70 students of the 2016 and 2017 batches of the Department of Biology Education, University of Muhammadiyah Malang. The two batches experienced different treatments; the 2016 batch took offline practicums, while the 2017 batch took practicums online due to the Covid-19 pandemic. The research instruments consisted of (1) student perception sheets, (2) tests, and (3) creative thinking skills assessment instruments. Data were analyzed descriptively and inferentially using one-way ANOVA and Hotelling's T2. The study results show students' perceptions of offline and online practicum. Students tend to understand the material better in offline practicum than online, and students also think that offline practicum is more interesting than online. Other findings indicate that students find it difficult to understand procedures in online practicums compared to offline ones. In addition, students experience technical problems in offline practicums, especially those related to networks. In contrast, technical issues can be overcome in online practicums because students can consult directly with practicum assistants. Analysis of student practicum results shows no difference between offline and online practicum results from the aspects of understanding and activeness. Meanwhile, from the aspect of report value, the online practicum is better than the offline one. This study also shows that students' creative thinking skills in offline practicums are higher than online in terms of the four aspects of creative thinking and three aspects of assessment, namely data analysis, work methods, and lists of references. In general, student perceptions, practicum results and creative thinking skills in offline practicums are better than in online ones.